Periodontal Research Wars: Navigating Through Minefield of Statistical Jargon - Shalini Mundra; Neetha J. Shetty; Srikant N; Aakash Agnihotri (Indian Journal of Forensic Medicine & Toxicology, 2022)
Statistical analysis is considered to be the backbone of research and however challenging it is to a clinician, it playsa crucial part for a researcher to comprehend the various presumptions underlying the statistical methods. In thefield of periodontology, statistical analysis is routinely used for management and interpretation of data. Yet, manyperiodontists find it difficult to understand the various statistical methods used in periodontal researches. Thus,this paper aims to cover the basictenetsof statistical analysisin a simplified manner with the help of flowcharts,specially emphasising on understanding few crucial points beforechoosing any statistical test. Later section of thearticle takes an application-based approach by incorporating the already illustratedflowcharts and crucial points.